THE EFFECT OF RETURN ON ASSSET, EARNING PER SAHRE, CURRENT RATIO AND RETURN IN EQUITY ON STOCK PRICE WITH PRIE EARNING RATIO AS A MODERATION ARRIABLE IN COMPANIES MANUFACTURING LISTED ON THE STOCK EXCHANGE INDONESIA PERIOD 2019-2022 - Yerlina Giawa; Hotni Ida Melati Tampubolon; Keumala Hayati; Dio Agung Herubawa (SEAN Institute, 2023)
This study aims to determine the effect of return on assets, earnings per share, current ratio and return on equity on stock prices with the price earning ratio as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. The sampling method in this study used a purposive sampling method and obtained as many as 50 samples that met the criteria from 177 companies that became the data in this study. The method used in this research is Moderate Regression Analysis. The results showed that return on assets, earnings per share, current ratio and return on equity, Price Earning Ratio (PER) partially affect stock prices. Price Earning Rato (PER) is not able to moderate the influence of Return On Assets (ROA), Current Ratio (CR) and Return On Equity (ROE) on stock prices.